Taxation Aspects, Information Asymmetry and Earnings Management : (Empirical Study on Goods and Consumer Goods Sector Listed on Indonesia Sharia Stock Index (ISSI) in 2016-2020 Period) - Fristanti, Vica; Senjani, Yayu Putri (Journal of Accounting Inquiry, 2022)
Purpose: The act of manipulating the presentation of financial statements by increasing or decreasing profits can be misleading and cause losses to other parties. Various factors motivate managers to take earnings management actions. This study aims to analyze earnings management actions by taking several indicators in terms of taxation aspects which include tax planning and deferred tax expense and indicators of information asymmetry owned by managers. Methodology: The objects used as research samples are manufacturing companies in the goods and consumption sector listed on the Indonesia Sharia Stock Index (ISSI) in 2016-2020. Companies were selected based on predetermined criteria using a purposive sampling method to obtain a sample of 130 observations. The analysis technique uses panel data regression which is processed with Eviews v.12 programs. Findings: The results show that tax planning, deferred tax expense and information asymmetry have a significant positive effect in detecting earnings management actions. Novelty: This study uses manufacturing companies in the goods and consumption sector as an object, and adds information asymmetry variable to the study. Furthermore, this study also measured earnings management by using the modified Jones model discretional accrual proxy.